A Formal Methodology for Accomplishing IEC 61850 Real-Time Communication Requirements - Kunz, Guilherme (2017)
Reliability is extremely important for control systems of energy distribution and generation. The IEC 61850 standard specifies an open architecture and communication protocols for such applications. The standard defines an open control architecture for networked control systems composed by intelligent electronic devices, stating some requirements that must be accomplished when developing reliable controllers for such systems. In this paper, we present a systematic and formal methodology to be adopted to achieve the correct implementation of the communication requirements of this standard. The methodology consists in five steps: modeling of real-time communication requirements defined by the standard; simulation of the obtained model; formal verification of the model, improved in the previous step; translation of the global model ( simulated and verified) into the input language of the real controller; and finally, application of conformance testing technique to the computational routine implemented in the real controller. Presented research deals with the proposition of a strategy to synthesize and validate models of systems developed under IEC61850 real-time requirements ( GOOSE and SMV) through simple operational conditions cases that, once validated, can be used in performance and conformance testing of more complex systems. The proposed methodology allows designers to synthesize reliable systems under IEC61850 real-time communication requirements.